Penggunaan teknik Fives dalam meningkatkan pemahaman membaca teks naratif di SMP - Raharjo, Subkhi Dwi (Jurnal Ilmiah WUNY, 2024)
This study aims to evaluate the effectiveness of the FIVES (Facts, Inferences, Vocabularies, Experiences, and Summary) technique in improving learning motivation and reading comprehension of narrative texts among 9th-grade students at Madrasah Mu'allimin Yogyakarta. The research background includes students' difficulties in understanding texts and finding information from readings, as well as the need to increase their learning motivation. The researcher employed Classroom Action Research (CAR) methodology, consisting of two cycles. Data were collected through test and non-test techniques (observation, questionnaires, and documentation), then analyzed using qualitative and quantitative methods. Results show a significant increase in English learning motivation after implementing the FIVES technique. Students became more enthusiastic about improving their narrative text reading skills. The average student scores also improved from 72.9 in Cycle I to 84.46 in Cycle II. In conclusion, the FIVES technique proves effective in enhancing students' learning motivation and reading comprehension of narrative texts. This research recommends using the FIVES technique as a good method for teaching reading skills.